2004
DOI: 10.1002/anie.200301749
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Peapods as Supramolecular Carbon Allotropes

Abstract: A high‐tech alternative to diamond and graphite: Supramolecular carbon allotropes are formed when single‐walled carbon nanotubes are filled with C60 molecules. Similar “molecular peapods“ are also obtained by insertion of endohedral fullerenes and metallocenes into carbon nanotubes. Supramolecular nanotubes built up from porphyrins can also encapsulate C60 peas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(36 citation statements)
references
References 42 publications
1
35
0
Order By: Relevance
“…Rao et al [111] have revealed the efficient growth of SWCNTs of diameter 1-3 nm from diamond nanoparticles and fullerenes. SWCNTs have stimulated intense theoretical and experimental studies due to their unique structural, mechanical, electronic, thermal and chemical properties, and their potential applications in diversified areas [112][113][114][115][116]. We studied the chemisorption of hydrogen atom (1 or 2H atoms) on the outer surfaces of the armchair SWCNTs [117][118][119].…”
Section: Cntsmentioning
confidence: 99%
“…Rao et al [111] have revealed the efficient growth of SWCNTs of diameter 1-3 nm from diamond nanoparticles and fullerenes. SWCNTs have stimulated intense theoretical and experimental studies due to their unique structural, mechanical, electronic, thermal and chemical properties, and their potential applications in diversified areas [112][113][114][115][116]. We studied the chemisorption of hydrogen atom (1 or 2H atoms) on the outer surfaces of the armchair SWCNTs [117][118][119].…”
Section: Cntsmentioning
confidence: 99%
“…Therefore, functionalization of CNTs with organic groups, which can enhance both the solubility in organic solvents and the number of reactive sites for post-integration into multicomponent organic materials, revealed to be the best approach to render these materials processable. [8][9][10][11] The main chemical approaches for the modification of CNTs are grouped into two categories: [12] i) non-covalent (or supramolecular) [13][14][15][16][17] and ii) covalent [8,[18][19][20] functionalization. While the supramolecular approach does not lead to a structural modification of the carbon framework, the covalent derivatization often leads to profound structural (and consequently electronic) alterations as a consequence of the change in the carbon hybridization.…”
Section: Introductionmentioning
confidence: 99%
“…(1) As is known (see reviews [2][3][4][5][6][7][8][9]), the stable hybrid (quasi-zero-dimensional + one-dimensional) nanostructures are formed at specific ratios between the nanotube and fullerene sizes: the "optimum" diameter D of the nanotubes used in the formation of nanopeapods with the participation of a particular type of fullerenes should be such that the distance between the nanotube wall and the fullerene cage corresponds to the characteristic lengths of van der Waals bonds. For boron-nitrogen nanostructures, this characteristic length corresponds to the distance between atomic networks in the structure of the hexagonal boron nitride; i.e., it is approximately equal to 3.33 Å.…”
Section: Models and Computational Methodsmentioning
confidence: 99%
“…The most popular representatives of the family of these "hybrid" (quasizero-dimensional + one-dimensional) systems are the carbon peapods C n @C-NT consisting of ordered onedimensional ensembles of C n ( n = 28-82) fullerenes encapsulated in carbon nanotubes. At present, considerable advances have been made in the investigation of the physical properties of the C n @C-NT peapods, which have very wide potential fields of application, from problems of fine chemical synthesis to the use as materials for accumulation and storage of hydrogen or for the design of superconductors (see reviews [2][3][4][5][6][7][8][9]). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation